2019
DOI: 10.1155/2019/2193453
|View full text |Cite
|
Sign up to set email alerts
|

Low-Abundance Dietzia Inhabiting a Water-Flooding Oil Reservoir and the Application Potential for Oil Recovery

Abstract: With the development of molecular ecology, increasing low-abundance microbial populations were detected in oil reservoirs. However, our knowledge about the oil recovery potential of these populations is lacking. In this study, the oil recovery potential of low-abundance Dietzia that accounts for less than 0.5% in microbial communities of a water-flooding oil reservoir was investigated. On the one hand, Dietzia sp. strain ZQ-4 was isolated from the water-flooding reservoir, and the oil recovery potential was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Tüccar et al 52 , found Pseudomonas as the dominant genus in produced water from Diyarbakir oil fields in Turkey.The authors suggested that these strains may have been inoculated into the oil reservoirs through the injection of produced water and that strains adapt to the conditions of the reservoir to survive. Several studies have found Pseudomonas in oil reservoirs 86 92 , and according to Cui et al 93 , Pseudomonas and Acinetobacter are genera that can effectively use crude oil as a carbon source, being able to survive and reproduce at the oil–water interface. Species of the genus Pseudomonas are facultative anaerobes capable of performing nitrification and nitrate reduction using various carbon substrates 94 , 95 .…”
Section: Resultsmentioning
confidence: 99%
“…Tüccar et al 52 , found Pseudomonas as the dominant genus in produced water from Diyarbakir oil fields in Turkey.The authors suggested that these strains may have been inoculated into the oil reservoirs through the injection of produced water and that strains adapt to the conditions of the reservoir to survive. Several studies have found Pseudomonas in oil reservoirs 86 92 , and according to Cui et al 93 , Pseudomonas and Acinetobacter are genera that can effectively use crude oil as a carbon source, being able to survive and reproduce at the oil–water interface. Species of the genus Pseudomonas are facultative anaerobes capable of performing nitrification and nitrate reduction using various carbon substrates 94 , 95 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 24 ] When using syngas as a probe, the peaks at 3018, 1304, and 2980–2855 cm −1 can be observed, which corresponds to CH 4 and CH x  species, respectively (Figure 5B); this is similar to the reported mechanism of the thermocatalytic CO hydrogenation. [ 24,25 ] In addition, the Co/SiO 2 was selected as a contrast sample and was prepared to measure in situ FT‐IR; as shown in Figure S11, Supporting Information, the peak at 1762 cm −1 is commonly assigned to the bridge‐bonded CO on the metallic Co 0 surface; the peak at 2856 and 1434 cm −1 corresponds to CH x  species and CH 3 , respectively [22b,25b,26] . Compared with Co/SiO 2 , the CO adsorption peak of the Co 1 Mn x /(MnO) 2 − x catalysts shifted to 1588 cm −1 , which indicated that the CO bond was weakened, and the adsorption of CO was promoted.…”
Section: Resultsmentioning
confidence: 99%
“…However, injection of the strain itself was not so successful, and field trials testing nutrient injection did not always result in an increase in the population of Dietzia sp. ZQ-4, indicating that an in-situ approach may not be viable although it may be possible to optimise this strategy further [72]. Biosurfactants produced by various rhodococci strains recovered from oil-polluted soils have been shown to be effective at recovering trapped oil from oil-saturated sand packs.…”
Section: Environmental Applicationsmentioning
confidence: 99%